Rotation sequence to report humerothoracic kinematics during 3D motion involving large horizontal component: application to the tennis forehand drive - Creveaux, T.; Sevrez, V.; Dumas, R.; Chèze, L.; Rogowski, I. (Sports Biomechanics, 2018)
The aim of this study was to examine the respective aptitudes of three rotation sequences (YtXf'Yh'', ZtXf'Yh'', and XtZf'Yh'') to effectively describe the orientation of the humerus relative to the thorax during a movement involving a large horizontal abduction/adduction component: the tennis forehand drive. An optoelectronic system was used to record the movements of eight elite male players, each performing ten forehand drives. The occurrences of gimbal lock, phase angle discontinuity and incoherency in the time course of the three angles defining humerothoracic rotation were examined for each rotation sequence. Our results demonstrated that no single sequence effectively describes humerothoracic motion without discontinuities throughout the forehand motion. The humerothoracic joint angles can nevertheless be described without singularities when considering the backswing/forward-swing and the follow-through phases separately. Our findings stress that the sequence choice may have implications for the report and interpretation of 3D joint kinematics during large shoulder range of motion. Consequently, the use of Euler/Cardan angles to represent 3D orientation of the humerothoracic joint in sport tasks requires the evaluation of the rotation sequence regarding singularity occurrence before analysing the kinematic data, especially when the task involves a large shoulder range of motion in the horizontal plane.